Sistema de informação para ajuste dos dados de tensão-deformação nos ensaios de compactação do solo - Lamb, Juliano Rodrigo (2006)
The soil compaction is a harmful phenomenon to the agricultural sector, intensified with the current model of culture adoption though the use of machines weighed in the culture systems, where these can exert superior pressures to the soil load support capacity. With the soil compaction and compression there is a reduction of the void ratios face to the air and water expulsion, that composes the system, harming the water absorption and minerals for the plants roots, as well as increasing the resistance of the ground to the penetration. By the way, it is formed becomes important the accomplishment of trials of compression for determination of the compaction levels, either in field through assays in situ or laboratory trials. The difficulty presented in trials of this nature, this related with the analysis of the gotten data and with the determination of the compression curves and stress point. Face this conjuncture one utilized the systems of information with the development of application of data base for the adjustment of the data of tension-deformation in trials in situ and laboratory. The system was developed using the environment of development Borland© Delphi© with data base Firebird and methodologies Oriented Objects and to 3Tier. With data proceeding from carried through trials, the software have demonstrated to efficiency in the reading and filtering of in situ trials data, security in the storage of all the referring data to the trials, as well as agility and precision in the determination of the curves of compression of the ground and in the esteem of the stress point. The results still allow concluding that, the traffic of machines in the activities in field intensify the phenomenon of the compaction, and that sinkage plate and oedometer are important in the accomplishment of trials of soil compression.